Electronic transport in torsional strained Weyl semimetals. (17th April 2018) - Soto-Garrido, Rodrigo; Muñoz, Enrique
Abstract: In a recent paper (Muñoz and Soto-Garrido 2017 J. Phys.: Condens. Matter 29 445302) we have studied the effects of mechanical strain and magnetic field on the electronic transport properties in graphene. In this article we extended our work to Weyl semimetals (WSM). We show that although the WSM are 3D materials, most of the analysis done for graphene (2D material) can be carried out. In particular, we studied the electronic transport through a cylindrical region submitted to torsional strain and external magnetic field. We provide exact analytical expressions for the scattering cross section and the transmitted electronic current. In addition, we show the node-polarization effect on the current and propose a recipe to measure the torsion angle from transmission experiments.